The Effect of Apple (Malus sylvestris) Varieties and Fermentation Time by Yeast Saccharomyces cerivisiae as Pre-Processing Treatment on Syrup Characteristics - Susanto, Wahono Hadi; Setyohadi, Bagus Rakhmad (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
Apple (Malus sylvestris Mill) is extensively produced in Batu â East Java. The apple varieties cultivated in Batu are Anna, Rome beauty, and Manalagi. Fermentation is aimed to obtain typical flavor of apple syrup. The purposed of this research was to determine the effect of apple varieties and time of fermentation on physicchemicaltic characteristics of apple syrup. This research used Randomized block Design with two factors. The first factor was apple varieties (Anna, Manalagi, Romebeauty) and the second factor was time of fermentation (9 hours, 12 hours, 15 hours) with 3 replications. The result showed that the apple varieties had different characteristics. Increasing fermentation time increased acidity, total soluble solute, reducing sugar concentration, antioxidant activity, and viscosity, meanwhile pH and vitamin C decreased. Apple varieties and fermentation time affected the preferences of taste, aroma and color of apple syrupKeywords: apple, apple syrup, fermentation, apple varieties